Tragic aesthetics: eighteenth-century tragedy and passive spectatorship. Issue 7 (10th November 2017) - Tierney-Hynes, Rebecca
ABSTRACT: This paper pursues the central thesis that the construction of the eighteenth-century spectator of tragedy as passive opens the self to a radical experience of otherness and a compassionate relationship to the public sphere. The paper examines two related arguments: first, that eighteenth-century tragedy and aesthetic autonomy are related, and that the persistent dismissal of eighteenth-century tragedy as effete and its audiences as complacently bourgeois might be overturned by another look at Adorno's ambivalent definition of aesthetic autonomy; second, that the tragedy of the early eighteenth century develops a special relationship to passivity, both onstage and in its characterisation of its own spectators, and that this passivity is understood to be a comment on tragic form. I conclude that passivity has a specific contemplative moral value in the early eighteenth century, and that its value is incorporated into ethical concepts of aesthetic apprehension.